Impact of Debt on the Economic Growth of Nepal - Baral, Rashmi; Phaju, Rajan (Khwopa Journal, 2023)
Public debt and Economic growth have always been the major topic of discussion in the Nepalese economy. Nepal, an underdeveloped country, is always trying to take a leap towards development but both external debt and domestic debt have been the major challenging tasks to perform in the economy. This study has empirically explored the relationship between foreign debt, internal debt and economic growth in Nepal. The time series data for the period of 1975-2021 AD has been applied. Unit root test with Augmented Dickey Fuller (ADF) model has been used to test data stationarity. The result of Autoregressive Distributed Lag (ARDL) model shows that internal debt has positive relationship with GDP whereas foreign debt has negative relationship with GDP. Toda-Yamamoto causality test method has been applied because of the non -stationarity of the data at level. The stationarity of data was seen only at first difference and second difference. Toda-Yamamoto Causality Test found the casual relationship between foreign debt, internal debt and economic growth in Nepal. The test is set at 5 percent level of significance. According to the results of the study, foreign debt and internal debt have unilateral relationship with GDP i.e. economic growth. This study shows there is long-run unidirectional causal relationship between foreign debt to GDP and also between internal debt to GDP in Nepal.